FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT BERINVESTASI SUKUK - Lilis Yuliati (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2011)
This study aims to analyze the interrelationship between risk factors and product attributes that affect the public interest in Islamic Sukuk invest SR001 and to know the appeal of an independent Islamic Bank Sukuk SR001 in selling by investors point of view. The method used in this study is a survey, while the sukuk investor respondens is SR 001, amounting to 100 people. The research was conducted by distributing questionnaires with Likert's scale. The analytical technique used is multiple regression. Based on the results of research and discussion that has been done can be concluded that the risk of investment and product islamic attributes positive effect on the public interest to invest, it is evident from the results of the test statistic, the test F and test T.